Pyrolysis of citrus wastes for the simultaneous production of adsorbents for Cu(II), H2, and d-limonene (2022)
A route based on pyrolysis and physical activation with H2O and CO2 was proposed to reuse citrus waste traditionally discarded. The citrus wastes were orange peel (OP), mandarine peel (MP), rangpur lime peel (RLP), and sweet lime peel (SLP). The main aim was to use the solid products of this new route as adsorbents for Cu(II) ions. Copper ions are among the most important water pollutants due to their non-degradability, toxicity, and bioaccumulation, facilitating their inclusion and long persistence in the food chain. Besides the solid products, the liquid and gaseous fractions were evaluated for possible applications. Results showed that the citrus waste composition favored the thermochemical treatment. In addition, the following yields were obtained from the pyrolysis process: approximately 30 % wt. of biochar, 40 % wt. of non-condensable gases, and 30 % wt. of bio-oil. The biochars did not present a high specific surface area. Nevertheless, activated carbons with CO2 and H2O presented specific surface areas of 212.4 m2/g and 399.4 m2/g, respectively, and reached Cu(II) adsorption capacities of 28.2 mg g−1 and 27.8 mg g−1. The adsorption kinetic study revealed that the equilibrium was attained at 60 min and the pseudo-second-order model presented a better fit to the experimental data. The main generated gases were CO2, which could be employed as an activating agent for activated carbon production. d-limonene, used for food and medicinal purposes, was the main constituent of the bio-oil.